2008
DOI: 10.1021/jp076561v
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Single-Walled Carbon Nanotubes and Polyethylene/Polypropylene/Polystyrene/Poly(phenylacetylene)/Poly(p-phenylenevinylene) Considering Repeat Unit Arrangements and Conformations:  A Molecular Dynamics Simulation Study

Abstract: Although there is plenty of research work being done in the field of carbon nanotube reinforced composite materials, no special attention has been paid to the factors of the polymer's repeat unit arrangement and conformation. In this paper we use molecular dynamics simulation based on a Condensed-phase Optimized Molecular Potentials for Atomistic Simulation Studies (COMPASS) force field to study the interactions between five types of polymers and (10, 10) single-walled carbon nanotubes (SWNTs). When we study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…These polymers have the addition of vinyl polymers, which are derived from popular monomers, such as methyl methacrylate copolymers, acrylic acid, acrylonitrile, styrene (ST), acrylamide, 4‐vinylpyridine, tetrafluoro ethylene, and poly( N ‐isopropylacrylamide) . Likewise, many polymers have been used, such as PVA, poly( N ‐vinyl pyrrolidone), poly(vinyl pyrrolidinone), poly(ethylene glycol), poly(vinylidene fluoride), poly( p ‐phenylenevinylene), polybenzoxazole, poly(styrene‐ co ‐acrylonitrile), ethyl vinyl alcohol copolymer, and polystyrene–polyisoprene diblock copolymer …”
Section: Nanocomposite Polymersmentioning
confidence: 99%
“…These polymers have the addition of vinyl polymers, which are derived from popular monomers, such as methyl methacrylate copolymers, acrylic acid, acrylonitrile, styrene (ST), acrylamide, 4‐vinylpyridine, tetrafluoro ethylene, and poly( N ‐isopropylacrylamide) . Likewise, many polymers have been used, such as PVA, poly( N ‐vinyl pyrrolidone), poly(vinyl pyrrolidinone), poly(ethylene glycol), poly(vinylidene fluoride), poly( p ‐phenylenevinylene), polybenzoxazole, poly(styrene‐ co ‐acrylonitrile), ethyl vinyl alcohol copolymer, and polystyrene–polyisoprene diblock copolymer …”
Section: Nanocomposite Polymersmentioning
confidence: 99%
“…Zheng and Xu also proposed that PE chains were covered along the tube axis before starting to kebab crystal growth . Some molecular dynamics simulation studies shown that the PE chains preferred to behave the extended conformation or ordered orientation structure along the tube axis in the first coating because of the strong van der Waals interaction between PE chains and CNTs . If the entropy penalty plays a main role in determining the polymer‐surface interaction, polymer adsorption will be controlled by orientation degree of polymer chains as it can reduce entropy penalty for adsorption on a surface.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, polymer chains can be adsorbed onto the surface of the carbon nanotube. This behavior could be favored in compounds that have benzene rings in the main chain, because they facilitate the parallel alignment between carbon nanotubes and the polymer matrix, or compounds with flexible groups facilitating polymer wrapping in carbon nanotubes …”
Section: Introductionmentioning
confidence: 99%